Prosthetic fungal infections: poor prognosis with bacterial co-infection. (May 2019) - Sidhu, M. S.; Cooper, G.; Jenkins, N.; Jeys, L.; Parry, M.; Stevenson, J. D.
Abstract : Aims: The aims of this study were to report the efficacy of revision surgery for patients with co-infective bacterial and fungal prosthetic joint infections (PJIs) presenting to a single institution, and to identify prognostic factors that would guide management. Patients and Methods: A total of 1189 patients with a PJI were managed in our bone infection service between 2006 and 2015; 22 (1.85%) with co-infective bacterial and fungal PJI were included in the study. There were nine women and 13 men, with a mean age at the time of diagnosis of 64.5 years (47 to 83). Their mean BMI was 30.9 kg/m 2 (24 to 42). We retrospectively reviewed the outcomes of these PJIs, after eight total hip arthroplasties and 14 total knee arthroplasties. The mean clinical follow-up was 4.1 years (1.4 to 8.8). Results: The median number of risk factors for PJI was 5.5 (interquartile range (IQR) 3.25 to 7.25). All seven patients who initially underwent debridement and implant retention (DAIR) had a recurrent infection that led to a staged revision. All 22 patients underwent the first of a two-stage revision. None of the nine patients with negative tissue cultures at the second stage had a recurrent infection. The rate of recurrent infection was significantly higher in the presence of multidrug-resistant bacteria (p = 0.007), a higher C-reactive protein (CRP) at the time of presentation (p = 0.032), and a higher number of co-infective bacterial organisms (p = 0.041). The overall rate of eradication of infection after two and five years was 50% (95% confidence interval (CI) 32.9 to 75.9) and 38.9% (95% CI 22.6 to 67), respectively. Conclusion: The risk of failure to eradicate infection with the requirement of amputation associated with this diagnosis is much higher than in patients with PJI without bacterial and fungal co-infection, and this risk is heightened when the fungal organism is joined by polymicrobial and multidrug-resistant bacterial organisms. Cite this article: Bone Joint J 2019;101-B:582–588.